Effectiveness of Motor Vehicle Tax Collection Services Through Samsat Outlets in the One-Roof Manunggal Administration System (SAMSAT) Office in the Takalar Region - Nur, Andi Cudai; Annisa, Ainun Husnun; Rukmana, Novayanti Sopia (Jurnal Aktor, 2023)
This study aims to determine the effectiveness of motor vehicle tax collection services through Samsat outlets at the Takalar Regional One-Stop Single Administration System (SAMSAT) Office and what supporting and inhibiting factors are faced in its optimization. This research uses a qualitative approach. Data collection carried out in this study is interactive data analysis through stages: data collection, data reduction, data presentation, and conclusion testing.The results of this study indicate that the effectiveness of motor vehicle tax collection services through Samsat outlets at the Takalar Region One-Stop Single Administration System (SAMSAT) office related to Efficiency is running quite well, Adequacy is running quite well, Equity is running well, Responsiveness is not running optimally or not running well and Accuracy is not running optimally or not running well. So it can be said that the effectiveness of motor vehicle tax collection services through Samsat Outlets at the Takalar Region One-Stop Single Administration System (SAMSAT) Office has not been running effectively in this case there are still acts of illegal levies committed by Samsat Outlet officers then samsat outlet officers have not been able to provide a quick response to complaints given by taxpayers in making motor vehicle tax payments. In addition, Samsat Outlet services have not had a significant impact on increasing and receiving motor vehicle tax targets.  Suggestion: The Takalar Regional Samsat Office, especially the North Galesong Samsat Outlet service, can improve the services provided to the taxpayer community so as to increase the number of users of Samsat Outlet services.